Respiratory virus infection among the children below 2 years in Nepal, 2019- A retrospective cross-sectional study (Journal of Pathology of Nepal, 2025)
Background: Acute respiratory infections of viral and bacterial origin pose serious problems owing to their great prevalence, with associated high morbidity and mortality.  In South Asia, acute respiratory acute respiratory infections cause about 15% of all pediatric deaths. Although infection rates are reported annually, there is limited information available regarding circulating respiratory pathogens. The aim was to determine the etiological agents of these respiratory diseases using multiplex molecular tests aiming to enhance knowledge on the circulation of viruses that causes acute respiratory infections in Nepal.Materials and Methods: This was a laboratory based retrospective cross-sectional study conducted from December 2020 to March 2021 on archived samples at National Influenza Center, Nepal, among children ≤2 years, who gave sample for influenza testing by the Dolphin system.Results: Of the 80 samples, 46 were positive. The most common was Respiratory Syncytial Virus A/B:13, followed by Adenovirus:12, Influenza A: 9, M. Pneumonia:4, ParainfluenzaVirus-3:4, Human Metapneumovirus Virus A/B, Human parechovirus, Rhinovirus, Influenza B :3, Para Influenza virus 4, Para Influenza Virus 2, Para Influenza virus 1 & Coronavirus 43:1. Also our result showed coinfectionin 11 samples of total tested samples.Conclusions: With a limited sample size, this study shows evidence of different pathogens that cause acute respiratory infection thus suggesting the need for community surveillance to enhance public health efforts and scientific understanding of respiratory infection for appropriate prevention, treatment & management strategies through strengthening molecular diagnostic methods which provide a rapid, sensitive and specific approach to improve the etiological diagnosis of infection.